The Attributes of Educators in Islam (Analysis of the Book of At Tarbiyah Al Amaliah by KH Imam Zarkasyi): Sifat-Sifat Pendidik dalam Islam (Analisis Kitab At Tarbiyah Al Amaliah Karya KH Imam Zarkasyi) - Mappanyompa, Mappanyompa; Muhlis, Muhammad; Sahwan, Sahwan; Saprun, Saprun (Halaqa: Islamic Education Journal, 2024)
This study focuses on exploring Islamic values, the characteristics of educators, and the concept of Islamic education through the analysis of the book "Kitab At Tarbiyah Al Amaliyah" by KH Imam Zarkasyi. The research methodology employed is a qualitative approach through a literature review, involving in-depth exploration and analysis of the content of the book as the primary source. The findings of the research indicate that Zarkasyi's thoughts on Islamic education emphasize Islamic values as the primary foundation in shaping the character and behavior of educators. The educator's qualities described in the book, such as sincerity, patience, and integrity, serve as practical guidelines for guiding students. Islamic education in Zarkasyi's concept not only encompasses academic dimensions but also represents a process of forming a resilient character. This research contributes to understanding the relevance of Islamic values in the context of modern education and how the concept of Islamic education can be effectively implemented. The research's conclusions and recommendations provide a foundation for further studies related to the implementation of Islamic values in educational practices and the adaptation of traditional educational methods to technological developments. Keywords: Islamic Education, Kitab At Tarbiyah Al Amaliyah, Educator's Qualities.